Sky Raiders [compact disc, unabridged] : - Mull, Brandon, 1974- (Mull, Brandon, 1974- Five Kingdoms, 2014)
Cole Randolph was just trying to have a fun time with his friends on Halloween (and maybe get to know Jenna Hunt a little better). A spooky haunted house turns out to be a portal to something creepy when Cole sees his friends whisked away to some mysterious place underneath the haunted house; he dives in after them, and ends up in The Outskirts. And once you come to the Outskirts, it's very hard to leave.